Llanos de Mojos, Bolivien. Die Wiederentdeckung des »Mound Velarde«. Die Arbeiten des Jahres 2019 - Prümers, Heiko; Jaimes Betancourt , Carla (e-Forschungsberichte des DAI, 2020)
More than 100 years ago swedish ethnologist Erland Nordenskiöld pioneered in the archaeology of the bolivian amazon lowlands. At Mound Velarde, a prehispanic settlement located on the land of the Estancia San Miguelito, he made the first stratigraphic observations in Bolivia. A detailed report of his work was published in 1913 leaving one thing open: the exact location of the site. In October 2019, surveys carried out in the region using LIDAR (Light detection and ranging) made it possible to identify the site.